P25 and P28 proteins of the malaria ookinete surface have multiple and partially redundant functions. - Tomas, A; Margos, G; Dimopoulos, G; van Lin, L; de Koning-Ward, T; Sinha, R; Lupetti, P; Beetsma, A; Rodriguez, M; Karras, M; Hager, A; Mendoza, J; et al. (2001)
The ookinete surface proteins (P25 and P28) are proven antimalarial transmission-blocking vaccine targets, yet their biological functions are unknown. By using single (Sko) and double gene knock-out (Dko) Plasmodium berghei parasites, we show that P25 and P28 share multiple functions during ookinete/oocyst development. In the midgut of mosquitoes, the formation of ookinetes lacking both proteins (Dko parasites) is significantly inhibited due to decreased protection against lethal factors, including protease attack. In addition, Dko ookinetes have a much reduced capacity to traverse the midgut epithelium and to transform into the oocyst stage. P25 and P28 are partially redundant in these functions, since the efficiency of ookinete/oocyst development is only mildly compromised in parasites lacking either P25 or P28 (Sko parasites) compared with that of Dko parasites. The fact that Sko parasites are efficiently transmitted by the mosquito is a compelling reason for including both target antigens in transmission-blocking vaccines.